Implementing lean production principles into the Nigerian construction industry - Olusegun, Adeyemo David, 1984-; Bachan Singh Besawa Jagar Singh, supervisor; Fakulti Kejuruteraan Awam (2012)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2012